Antimalarial drug resistance profiling of Plasmodium falciparum infections in India using Ion Torrent deep sequencing - Kale, Sonal; Uplekar, Swapna M.; Bandyopadhyay, Nabamita; Rao, Pavitra N.; Ali, Syed Z.; Sharma, Surya Kant; Tandel, Nikunj; Patel, Ankita; Singh, Ranvir; Dank, Aaron; Ravishankaran, Sangamithra; Priya, G. Sri Lakshmi; et al. (Frontiers in Malaria, 2024)
Introduction: Tracking the emergence and spread of antimalarial drug resistance is critical for supporting progress towards the control and eventual elimination of malaria in South Asia, especially India. Plasmodium falciparum has evolved resistance to virtually every antimalarial drug, and significant progress has been made to identify the molecular genetic mechanisms involved in the most common types of resistance. Methods: An amplicon sequencing protocol was used for molecular surveillance of antimalarial drug resistance in a total of 158 patient isolates collected from December 2012 to September 2015 from three sites in south, west and east India: Tamil Nadu, Gujarat, and Odisha respectively. Five full length Plasmodium falciparum genes whose mutant proteins are implicated in antimalarial drug resistance were investigated: Pfcrt for chloroquine, Pfdhfr for pyrimethamine, Pfdhps for sulfadoxine, Pfk13 for artemisinin and Pfmdr1 for resistance to multiple antimalarial drugs. Results: We observed a high proportion of wild-type Pfcrt and Pfdhfr haplotypes from the P. falciparum-dominant site Rourkela, while mutant Pfcrt and Pfdhfr haplotypes were fixed at the P. vivax dominant sites Chennai and Nadiad. The wild-type Pfdhps haplotype was predominant across all study sites. We identified mutations in the propeller domain of Pfk13, although they are not associated with resistance to artemisinin. Finally, using samples taken from the same patient on day 2, day 7, and day 14 after artemisinin combination treatment, we were able to observe changes in allele frequency of drug resistance genes during the course of an infection. Discussion: This is the first high-throughput deep sequencing study of five full-length P. falciparum genes in clinical isolates from three different study sites in India with varying transmission ecologies. Amplicon sequencing based on ion-torrent has the potential to track changes in the frequency of drug resistant alleles as a patient is undergoing drug therapy, and to identify new resistance mutations as they increase in frequency in the patient. This study showed possibility of whole gene sequencing, leads to in-depth molecular surveillance of multiple antimalarial resistant candidates and furthermore suggests investigations on reversal of resistant genotypes due to usage of artemisinin combination therapy in P. falciparum prevalent areas of the country.